Evaluation of Performance of the Non-Cash Food Assistance (BPNT) Program in Meeting the Basic Needs of Poor and Vulnerable Communities - Hijriatul Mabruk; Eko Prasojo (Journal Research of Social Science, Economics, and Management, 2024)
The BPNT program is a social assistance fund that is given in the amount of 200 thousand rupiah per family per month to buy food. In the implementation of the 2022 Fiscal Year, the BPNT Program has achieved a realization performance of 99.25 percent and a budget realization of 98.15 percent. This realization still needs to be analyzed in more depth using six criteria from Dunn's (2017) evaluation theory to find out whether the program is effective in achieving the planned program goals. This research is descriptive qualitative research based on the collection of data and secondary sources through literature review and expert opinions, as well as documentation studies. The results of the study show that from the aspects of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy, the BPNT Program has a positive impact and trend on the poor and vulnerable. However, the implementation of this program still has shortcomings, including the lack of program socialization, a list of beneficiaries that is not updated, and a lack of equity, as well as the accuracy of beneficiaries. Recommendations that can be given are to be sought so that the BPNT Program continues to run and continue; conducting evaluation and improvement efforts, as well as updating beneficiary data; and improving the quality of services and information to beneficiaries; In the future, the BPNT Program can be in the form of community empowerment programs; As well collaborating with other ministries and/or agencies, as well as the private sector to provide more optimal services.